La gobernanza y el código de ética en la gestión pública del GAD municipal del cantón Pastaza - Guevara Moya, Josué Enrique (2024)
ABSTRACT: Governance constitutes a set of institutional conveniences that prepare, adopt and execute public decisions in an explicit social environment. On the other hand, the question of ethics appears together with important reforms in the State and specifically when it is related to Public Administration. For this reason, the objective of this research is to determine the implication of governance and the code of ethics in the development of public management in the Municipal Government of Pastaza. To achieve this objective, a correlational and descriptive methodology was used, with a non-experimental design and a mixed approach, since both an interview and a survey were used in a complementary manner. From the instruments used, data were obtained to test the hypothesis, and the null hypothesis was rejected. It is concluded that governance and the code of ethics have great relevance with public management, and that among the characteristics of these variables in the development of public management of the Municipal Government of Pastaza, the elaboration and application of pertinent public policies was identified; their implementation and evaluation carried out jointly by the government, the private sector and the civil society.